Critical assessment of the ubiquitous occurrence and fate of the insect repellent N,N-diethyl-m-toluamide in water - Merel, Sylvain; Snyder, Shane A. (Environment international, 2016)
The insect repellent diethyltoluamide (DEET) is among the most frequently detected organic chemical contaminants in water across a wide range of geographies from around the world. These observations are raising critical questions and increasing concerns regarding potential environmental relevance, particularly when the emergence of severe neurological conditions attributed to the Zika virus has increased the use of insect repellents. After dermal application, DEET is washed from the skin when bathing and enters the municipal sewer system before discharge into the environment. Mainly measured by gas chromatography or liquid chromatography coupled to mass spectrometry (GC‐MS or LC-MS), more than 200 peer-reviewed publications have already reported concentrations of DEET ranging ng/L to mg/L in several water matrices from North America, Europe, Asia, Oceania, and more recently Africa and South America. While conventional wastewater treatment technology has limited capacity of removal, advanced technologies are capable of better attenuation and could lower the environmental discharge of organic contaminants, including DEET. For instance, adsorption on activated carbon, desalinating membrane processes (nanofiltration and reverse osmosis), ozonation, and advanced oxidation processes can achieve 50% to essentially 100% DEET attenuation. Despite the abundant literature on the topic, the ubiquity of DEET in the environment still raises questions due to the apparent lack of obvious spatio-temporal trends in concentrations measured in surface water, which does not fit the expected usage pattern of insect repellents. Moreover, two recent studies showed discrepancies between the concentrations obtained by GC‐MS and LC-MS analyses. While the occurrence of DEET in the environment is well established, the concentrations reported should be interpreted cautiously, considering the disparities in methodologies applied and occurrence patterns observed. Therefore, this manuscript provides a critical overview of the origin of DEET in the environment, the relevant analytical methods, the occurrence reported in peer-reviewed literature, and the attenuation efficacy of water treatment processes. [Display omitted] •DEET is detected in Africa, America, Asia, Europe and Oceania.•DEET is detected in all types of water matrices, from landfill leachate to drinking water.•Frequent detection of DEET in blanks•Advanced wastewater treatment can improve the attenuation of DEET.•An analytical interference or the occurrence of a mimic are not excluded when measuring DEET.